Automated temperature and humidity control and monitoring system for improving the performance in drying system - Alkahdery, L. A.; Yurchenko, Alexey V.; Mohammed, J. A.-K; Neshina, Elena G. (Eurasian physical technical journal)
Temperature and relative humidity are the key control parameters in drying processes for preserving and improving food quality. To achieve this goal, an automatic control system has been designed and built to provide adequate heat and drying streams according to the ambient requirements of various climatic zones and the kind of dried product. The control system combined with sensors allows the temperature and humidity of the drying chamber to be adjusted online by predetermined parameters. When there is little or no radiation present or when rapid drying rates are required, the heated air stream may be produced utilizing an electric motor fan in addition to an electrical backup heater. The fan automatically modifies its speed using the Pulse Width Modulationtechniquefor energy efficiency depending on the required temperature of the drying chamber. The control system based on Arduino Uno board is built within the solar dryer, after which tests are carried out. The test results are displayed on a display. Themanagement system was set up to maintain an ambient temperature between 40 and 60 °C andrelative humidity between 10 and 20 %. The system is a flexible solution for different climatic zones and dried products, according to experimental findings demonstratingits efficiency in managing the drying environment. Finally, this paper can conserve energy because it only works when the temperature around the food is below 60 oC.